Developing a core competency framework for advanced practice nursing in mainland China: a sequential exploratory study - Hongxia Guo; Wei Zhu; Jiping Li (BMC, 2023)
Abstract Background Advanced Practice Nursing (APN) have been highly valued and an integral part of the health care system. Development and establishment of new APN roles is a complex process that has resulted from a wide variety of reasons, key component is a lack of a competency map delineation and role evaluation. Currently, however, competence framework has not been compared at an international level. In mainland China, APN have been introduced in some organizations but their competency domains have not yet been clearly defined, this study aimed to identify the core competencies for advanced practice nursing. Methods This study was performed in two phases: first, in-depth and semi-structured individual interviews with 46 participants from key stakeholders were carried out followed by a qualitative content analysis, then an item pool of core competencies was constructed by extracting data from the first phase and the results from previous studies, scales and documents; second, a Delphi technique was conducted with the participation of 28 experts from 7 areas of China to form the final core competency framework for advanced practice nursing. Results Through the qualitative phase, the core competency framework with six domains and 70 items emerged and then entered into the Delphi phase. Twenty-eight of 30 experts finished 2 rounds of Delphi approaches. The final core competencies for advanced practice nursing consisted of six domains with 61 items, including direct clinical nursing practice, research and evidence-based nursing practice, professional development, organization and management, mentoring and consultation, and ethical/legal practice. Conclusion This core competency framework consisted of six domains with 61 items can be used in competency-based education to cultivate advanced practice nurses as well as competency level assessment.